Identification of marine key areas across the Caribbean to ensure the conservation of the critically endangered hawksbill turtle. (July 2018) - Nivière, Manon; Chambault, Philippine; Pérez, Thierry; Etienne, Denis; Bonola, Marc; Martin, Jordan; Barnérias, Cyrille; Védie, Fabien; Mailles, Julien; Dumont-Dayot, Émilie; Gresser, Julie; Hiélard, Gaëlle; et al.
Abstract: Acquisition of data on animal movement when developing management strategies is a common challenge in species conservation, especially when dealing with a critically endangered species as the hawksbill turtle Eretmochelys imbricata . To reach the objective of the 2008 national action plan for Martinique Island (French West Indies), the present paper examines horizontal and vertical movements in juveniles ( n = 3) and adults life stages (11 females and 2 males) of 16 hawksbill turtles. Our results reveal the strong site fidelity of individuals to their foraging grounds (mean male foraging home range: 89.3 ± 20.2 km 2, mean female foraging home range: 336 ± 284.7 km 2, mean juvenile foraging home range: 157.3 ± 71.2 km 2 ) and to the females' inter-nesting areas (mean home range: 284.2 ± 523.7 km 2 ). A spatial foraging overlap occurred between juveniles and males as they shared 41% of their 95% kernel foraging habitat. The turtles performed mainly long and shallow dives within the first 20 m deep around Martinique Island, occupying shallow waters close to shore. The migratory routes of the adult females revealed regional connectivity between the Caribbean islands, crossing 31 exclusive economic zones and international waters, and featuring distinct foraging grounds. This finding reinforces the significance of a cooperative network at the Caribbean scale to ensure the efficient conservation of this critically endangered species.